2016
DOI: 10.18632/oncotarget.8629
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26b inhibits tumor metastasis by targeting the KPNA2/c-jun pathway in human gastric cancer

Abstract: MicroRNAs (miRNA) play an important role in carcinogenesis. Previously, we identified miR-26b as a significantly downregulated miRNA in gastric cancer (GC) tissues (n = 106) based on differential quantitative RT-PCR (RT-qPCR) miRNA expression profiles. In the current study, we aimed to clarify the potential role of miR-26b and related target genes in GC progression. Downregulation of miR-26b was associated with advanced tumor-node-metastasis stage (TNM stage) and poor 5-year survival rate. Forced expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…Similarly, the inhibitory roles of various miRNAs in tumor growth and metastasis have been demonstrated in previous NSCLC studies [ 30 , 38 , 39 ]. Furthermore, upregulation of miR-26b leads to inhibition of gastric cancer cell migration and invasion in vitro and lung metastasis formation in vivo [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the inhibitory roles of various miRNAs in tumor growth and metastasis have been demonstrated in previous NSCLC studies [ 30 , 38 , 39 ]. Furthermore, upregulation of miR-26b leads to inhibition of gastric cancer cell migration and invasion in vitro and lung metastasis formation in vivo [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-26a functions in cardiovascular diseases by controlling multiple signaling pathways related to angiogenesis, endothelial cell growth, and left ventricle function after myocardial infarction. Analysis of miR-26 family members in different types of cardiac cells [52-54], including endothelial cells, vascular smooth muscle cells, cardiomyocytes, and cardiac fibroblasts, has shown that miR-26 may have important functions in various cardiovascular repair mechanisms [55, 56]. Intriguingly, miR-26a has was also been found to negatively regulate glycogen synthase kinase (GSK) 3β expression, thereby altering Wnt signaling by modulating the levels of β-catenin and its downstream target C/EBPα during osteogenesis differentiation [57, 58].…”
Section: Mirna Biogenesis and Functionmentioning
confidence: 99%
“…NMI, another novel interactor of GART, negatively regulates epithelial-mesenchymal transitions by inhibiting p65 acetylation in the NF-Kβ pathway (166). Knockdown of KPNA2, a novel interactor of GART, suppresses the proliferative and migratory abilities of lung cancer cells and downregulation of its regulatory miRNA miR-26b enhances cell migration and invasion in vitro, and metastasis in vivo (167). One of the downstream targets of KPNA2, which is overexpressed in non-small cell lung cancer, is another novel interactor of GART called JUN, a component of the transcription factor AP-1 promoting progression of cell cycle and involved in breakdown of the ECM (168).…”
Section: Novel Interactions Of Ifnar1 and Gart May Point At The Influmentioning
confidence: 99%